Mikołaj Rej and his “Kupiec” and Religious Topics on the Polish Stage - Bering, Piotr (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The present paper focuses on the Polish religious polemic during the first phase of the Reformation period. Today we know only a few plays from this period. Fortunately, they do allow us, nevertheless, to analyse the main topic and to reconstruct their hypothetical staging.